VIRAL BIOSAFETY OF BIOPHARMACEUTICALS - D. A. Gusarov (Разработка и регистрация лекарственных средств, 2019)
Therapeutics produced by eukaryotic cell lines could possible be contaminated with bioburden; the most dangerous for human is viral contamination. The article describes the problem of viral safety of biopharmaceuticals. The strategy of downstream process steps for the viral safety guarantee is discussed. The methods of viral inactivation, filtration, purification are given in the paper.